Efek Daun Alpukat (Persea Americana M.) dan Daun Kelor (Moringa Oleifera L.) terhadap Peningkatan Kadar HDL Pada Model Tikus Putih Hiperlipidemia - Handayani, Sri; Saryono; Hernayanti (Jurusan Keperawatan FIKES UNSOED, 2017)
Hyperlipidemia is a lipid metabolism disorder which is characterized by decreasing of High Density Lipoprotein (HDL) level. Avocado (Persea americana) and Kelor (Moringa oleifera) leaves can be proposed for increasing HDL level. This research aimed to determine the steeping combination of avocado and kelor leaves effect to against HDL level for hyperlipidemia rat model. This research used true experimental pre and post test with control design. Amount of 36 rats were divided into negative control (A), single dose of Persea leaves steeping 36mg/200gramBB (B), combination of 36mg/200gramBW Persea leaves and 54 mg/200gramBW Moringa leaves (C), combination of 18mg/200gramBB Persea leaves and 27 mg/200gramBW Moringa leaves (D), single dose of Moringa leaves steeping 54mg/200gramBW (E), and simvastatin 0,018 mg/day (F). Data were analyzed by ANOVAÃ‚Â test and continued by Duncan post-hoc test. ANOVA tests showed there are significant differences bethween group (p = 0.008). Duncan post hoc test showed that the combination group and simvastatin control group are equally strong to increase HDL levels. The steeping combination of Persea and Moringa leaves has an effect to increasing HDL level.